Safety of Immunizations for the Adult Patient With Inflammatory Bowel Disease—A Systematic Review and Meta-analysis. Issue 9 (24th November 2021) - Desalermos, Athanasios; Pimienta, Michael; Kalligeros, Markos; Shehadeh, Fadi; Diamantopoulos, Leonidas; Karamanolis, George; Caldera, Freddy; Farraye, Francis A
Abstract: Background: Patients with inflammatory bowel disease (IBD) have low vaccination rates for vaccine-preventable diseases. Fear of adverse reactions (AEs) appear to negatively affect vaccination efforts. We aimed to systemically review the risks for AEs following immunization for patients with IBD. Methods: We searched PubMed and Embase until April 15, 2020, for studies evaluating the safety of vaccinations among patients with IBD. The primary outcome was the incidence of systemic and local AEs among vaccinated patients. Secondary outcome was the rate of IBD flare following immunization. We utilized a random effects meta-analysis of proportions using the DerSimonian-Laird approach to estimate the safety of immunizations. Results: A total of 13 studies with 2116 patients was included in our analysis after fulfilling our inclusion criteria. Seven studies examined the influenza vaccine, 4 the pneumococcal vaccine, 1 the recombinant zoster vaccine, and 1 the hepatitis B vaccine. Follow-up of patients was up to 6 months. The majority of AEs were local, with a pooled incidence of 24% (95% CI, 9%-42%) for all vaccines. Systemic AEs were mostly mild, without resulting in hospitalizations or deaths, with a pooled incidence of 16% (95% CI, 6%-29%) for all vaccines. Flare of inflammatory bowel disease after vaccination found with a pooled incidence of 2% (95% CI, 1%-4%) and we include in the analysis data from all immunizations examined. Discussion: Our study demonstrated that AEs after vaccination are mainly local or mildly systemic and do not differ significantly from the expected AE after recommended immunizations for the general population. Thus, gastroenterologists should reinforce that vaccines are safe in patients with IBD.